2002
DOI: 10.1007/s00415-002-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil in treatment of fatigue in multiple sclerosis

Abstract: Treatment with modafinil significantly improves fatigue and sleepiness and is well tolerated by patients with MS. Unlike the higher dose regimen required in narcolepsy, a low-dose regimen of modafinil is effective in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
5
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(101 citation statements)
references
References 35 publications
3
88
5
5
Order By: Relevance
“…Fatigue was also associated with reduced sexual desires in MS patients (Zifko, 2003). Other studies have shown how yoga training was used to reduce fatigue and improve MS patients' sleep quality (Sookcharoen, 2001;Wood, 1993), and because sleep is one of the most important fatigue related factors among the MS patients, it seems prudent to consider yoga for its multidimensional benefits.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fatigue was also associated with reduced sexual desires in MS patients (Zifko, 2003). Other studies have shown how yoga training was used to reduce fatigue and improve MS patients' sleep quality (Sookcharoen, 2001;Wood, 1993), and because sleep is one of the most important fatigue related factors among the MS patients, it seems prudent to consider yoga for its multidimensional benefits.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Zifko (2003) in the United States, 70-90% of MS patients reported symptoms of pain and fatigue, 50-60% perceived fatigue which prohibited the scope of their activities of daily living. Fatigue was also associated with reduced sexual desires in MS patients (Zifko, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…14 Several small studies have found that treatment with modafinil, a wake-promoting agent, improved symptoms of MS fatigue, although in a larger randomized controlled trial there was no difference. [15][16][17] These studies did not use objective measures of alertness. Beyond these pharmaceutical studies, little research has been conducted into whether poor sleep and decreased alertness are major determinants of MS fatigue.…”
Section: Original Articlementioning
confidence: 99%
“…Fatigue or weakness can also make navigating long distances difficult for a wheelchair user. Diagnoses that can produce muscle fatigue or weakness include MS (43%-90% of cases) [4,36], severe TBI (37%-50%) [54,57], and ALS (26%) [16].…”
Section: Upper-body Physical Impairmentmentioning
confidence: 99%
“…Of people with MS, 85 percent reported gait and motor disturbances as their primary complaint [32]. Symptoms that are relevant to wheelchair use include spasticity, tremors, fatigue, ataxia, and impaired executive reasoning [4,25,[33][34][35][36].…”
Section: Multiple Sclerosismentioning
confidence: 99%